2015
DOI: 10.1016/j.fsi.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the TNF superfamily members CD40L and BAFF in the small-spotted catshark ( Scyliorhinus canicula )

Abstract: The tumour necrosis factor superfamily (TNFSF) members CD40L and BAFF play critical roles in mammalian B cell survival, proliferation and maturation, however little is known about these key cytokines in the oldest jawed vertebrates, the cartilaginous fishes. Here we report the cloning of CD40L and BAFF orthologues (designated ScCD40L and ScBAFF) in the small-spotted catshark (Scyliorhinus canicula). As predicted both proteins are type II membrane-bound proteins with a TNF homology domain in their extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…This last set of data by Yong-Feng Gong et al elegantly demonstrated that the interaction between T and B cells through ligation of CD40 elicits TD immune responses in fish. Studies on the small-spotted catshark paralleled these results, showing that CD40L was mainly expressed in the spleen, as well as in the mucosal tissues, such as gills and gut ( 131 ). The transcription of CD40L was significantly upregulated after the addition of T cell polyclonal activators to cultures of PBL in vitro .…”
Section: Cd40l and Ox40lmentioning
confidence: 83%
See 2 more Smart Citations
“…This last set of data by Yong-Feng Gong et al elegantly demonstrated that the interaction between T and B cells through ligation of CD40 elicits TD immune responses in fish. Studies on the small-spotted catshark paralleled these results, showing that CD40L was mainly expressed in the spleen, as well as in the mucosal tissues, such as gills and gut ( 131 ). The transcription of CD40L was significantly upregulated after the addition of T cell polyclonal activators to cultures of PBL in vitro .…”
Section: Cd40l and Ox40lmentioning
confidence: 83%
“…The homologue sequences to mammalian BAFF have been reported in many teleost fish species including rainbow trout ( 41 ), zebrafish ( 120 ), mefugu ( Takifugu obscurus ) ( 121 ), Japanese sea perch ( Lateolabrax japonicus ) ( 122 ), grass carp ( Ctenopharyngodon idella ) ( 123 ), yellow grouper ( Epinephelus awoara ) ( 124 ), miiuy croaker ( Miichthys miiuy ) ( 125 ), tongue sole ( Cynoglossus semilaevis ) ( 126 ), Nile tilapia ( Oreochromis niloticus ) ( 127 ), rock bream ( Oplegnathus fasciatus ) ( 128 ), and also in cartilaginous fish such as white-spotted catshark ( Chiloscyllium plagiosum ) ( 129 ), spiny dogfish ( Squalus acanthias ) ( 130 ), and small-spotted catshark ( Scyliorhinus canicula ) ( 131 ) (summarized in Table 3 ). Interestingly, some studies have revealed that many cartilaginous and bony fish species have more than one BAFF gene ( 51 , 54 ), representing two distinct groups.…”
Section: B Cell-activating Factor Of the Tnf Familymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BAFF sequences have been reported in different teleost fish species including zebrafish ( Danio rerio ) (21), mefugu ( Takifugu obscurus ) (22), Japanese sea perch ( Lateolabrax japonicus ) (23), grass carp ( Ctenopharyngodon idella ) (24), yellow grouper ( Epinephelus awoara ) (25), miiuy croaker ( Miichthys miiuy ) (26), tongue sole ( Cynoglossus semilaevis ) (27), Nile tilapia ( Oreochromis niloticus ) (28), rock bream ( Oplegnathus fasciatus ) (29), and cartilaginous fish such as white-spotted catshark ( Chiloscyllium plagiosum ) (30), spiny dogfish ( Squalus acanthias ) (31), and small-spotted catshark ( Scyliorhinus canicula ) (32). Although recombinant BAFF proteins have been produced for some of these species (2123, 25, 2730), many of these studies have exclusively tested the effect of recombinant fish BAFF on B cell survival using mammalian B cells (21, 22, 25, 28, 30).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the BAFF and APRIL subfamily of ligands and receptors, BAFF sequences have been reported recently in different teleosts including zebrafish ( Danio rerio ) [9], mefugu ( Takifugu obscurus ) [10], Japanese sea perch ( Lateolabrax japonicus ) [11], grass carp ( Ctenopharyngodon idella ) [12], yellow grouper ( Epinephelus awoara ) [13], miiuy croaker ( Miichthys miiuy ) [14], tongue sole ( Cynoglossus semilaevis ) [15], Nile tilapia ( Oreochromis niloticus ) [16], rock bream ( Oplegnathus fasciatus ) [17], rainbow trout ( Oncorhynchus mykiss ) [18], rohu ( Labeo rohita ) [19] and cartilaginous fish such as white-spotted catshark ( Chiloscyllium plagiosum ) [20], spiny dogfish ( Squalus acanthias ) [21] and small-spotted catshark ( Scyliorhinus canicula ) [22]. APRIL sequences, on the other hand, have only been identified in channel catfish ( Ictalurus punctatus ), Atlantic salmon ( Salmo salar ) and rainbow trout [18, 22]. Interestingly, in species such as rainbow trout, a cytokine designated as a BAFF and APRIL-like molecule (BALM) has also been reported [18].…”
Section: Introductionmentioning
confidence: 99%